The Te Kāhui Kuhukura wellbeing index - John Reid; Amanda Yates (Nature-Based Solutions)
Place-based, Indigenous ways of knowing have real relevance in a context of urban system change. Indigenous approaches have developed over time in places that are understood as ecological entities and venerated kin, not geological resource. Such socio-ecological and nature-responsive models are evidenced to offer the adaptive, ecologically ethical and responsive strategies needed at this time of complex ecological crisis. The research discussed here is founded in a complex Indigenous wellbeing concept – mauri ora - that links social and ecological wellbeing together as an indissoluble whole. Earlier research developed an urban mauri-centered “compass” that oriented users towards nature-based and socio-ecological approaches to urban wellbeing. An urban wellbeing data display was also developed that measured and visualised current states of social, cultural and ecological wellbeing. This mauri-centered research methodology was then tested out in place, in Waitaha/Canterbury, in the South Island of Aotearoa, New Zealand. Working with Te Kāhui Kahukura, a group of Māori Iwi kin authorities, a wellbeing index was developed. In this paper we describe the research context, the place-based index and its key domains and measures that assess socio-ecological wellbeing as a complex whole in the context of urban environments.